Perlindungan Hukum Bagi Usaha Waralaba di Indonesia Berdasarkan Hukum Perdata - Tri Naili, Yuris (Faculty of Law, Universitas Pekalongan, 2024)
Franchise businesses are a rapidly growing form of enterprise that significantly contribute to the national economy. However, in practice, various legal issues arise, such as unclear contractual clauses, intellectual property rights violations, and disputes between franchisors and franchisees. This study aims to analyze the legal protection of franchise businesses in Indonesia based on civil law. It employs a normative juridical approach, analyzing relevant regulations, including Government Regulation No. 42 of 2007, Minister of Trade Regulation No. 53/M-DAG/PER/8/2012, and the Indonesian Civil Code. The findings reveal that franchise agreements in Indonesia are clearly regulated under Government Regulation No. 42 of 2007, providing legal certainty for both franchisors and franchisees through written contracts. These contracts detail the rights, obligations, and responsibilities of each party, including critical aspects such as intellectual property rights (IPR), training, operational support, and the franchisee's obligation to operate the business according to established standards. Legal protection for franchise businesses is rooted in various regulations, including the Civil Code, which recognizes franchise agreements as reciprocal obligations. IPRs, such as trademark rights, patents, copyrights, and trade secrets, play a crucial role in protecting business elements that enhance competitiveness, including brands, technical innovations, and business concepts. Challenges in legal protection for franchise agreements in Indonesia involve several issues. One such issue is the failure to register franchise agreements, which can render them legally invalid. Additionally, unilateral termination by franchisors can harm franchisees. Trademark violations, such as unauthorized use, may also cause losses for both parties. Imbalances in bargaining positions between franchisors and franchisees often result in unfair contracts, potentially undermining the principle of freedom of contract in civil law